Interferon-α-Enhanced CD100/Plexin-B1/B2 Interactions Promote Natural Killer Cell Functions in Patients with Chronic Hepatitis C Virus Infection - He, Yu; Guo, Yonghong; Fan, Chao; Lei, Yingfeng; Zhou, Yun; Zhang, Mingjie; Ye, Chuantao; Ji, Guangxi; Ma, Li; Lian, Jianqi; Moorman, Jonathan P.; Yao, Zhi Q.; et al. (Frontiers in Immunology, 2017)
Background CD100, also known as Sema4D, is an immune semaphorin constitutively expressed on natural killer (NK) cells and T cells. As an immune activation molecule, CD100 has important immunoregulatory effects on NK functions by enhancing the interactions between NK cells and target cells. The aim of this study was to investigate whether hepatitis C virus (HCV) infection affects CD100 expression, and whether interferon-α treatment enhances NK killing activity to facilitate HCV clearance via CD100. Methods Expression of CD100 on NK cells was evaluated by flow cytometry in patients with chronic HCV infection, with or without pegylated interferon-α-based therapy. NK cell cytotoxicity and interferon (IFN)-γ production were measured by flow cytometry upon culturing the NK cells with K562 and Huh7.5 or HCV JFH-1-infected Huh7.5 cells. Results The frequency of CD100+ NK cells in HCV-infected individuals was slightly suppressed compared to healthy subjects. IFN-α treatment could significantly upregulate CD100 expression, which was confirmed by in vitro studies using peripheral blood mononuclear cells cocultured with HCV-expressing Huh7.5 cells or IFN-α. Importantly, the expression of CD100 on NK cells from HCV patients was inversely associated with the HCV-RNA levels in the early phase of IFN-α therapy, and the IFN-α upregulated CD100 led to an enhanced NK killing activity through ligations with its receptors plexin-B1/B2 on target cells. Conclusion These results implied a novel mechanism by which IFN-α enhanced CD100/Plexin-B1/B2 interaction plays an important role in promoting NK functions in patients with chronic hepatitis C.